Genetic analysis of general characters of granular starch quality in the maize based on the mutation SU2 - Тимчук, С. М.; Мартинюк, М. М.; Поздняков, В. В.; Тимчук, В. М.; Анциферова, О. В.; Харченко, Ю. В.; Харченко, Л. Я. (Scientific Progress & Innovations, 2012)
It has been established that the general characters of granular starch quality in the maize based on the mutation SU2 were notable as having the quantitative nature. Inbreds – carriers of this mutation differ from each other in the effects of combining abilities for the starch granules diameter, starch in the grain and amylose in the grain contents. The starch granules diameter and starch content in the grain were inherited by the carriers of mutation SU2 according to the type of positive over–dominance, and the content of amylose in the starch – according to the type of incomplete dominance with the significant contribution of additive effects to the dispersion.